2009
DOI: 10.1118/1.3183501
|View full text |Cite
|
Sign up to set email alerts
|

Multiple scattering of 13 and 20 MeV electrons by thin foils: A Monte Carlo study with GEANT, Geant4, and PENELOPE

Abstract: All the codes give a reasonable agreement (within 5%) with the experimental results for all the material and thicknesses studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…This cut-off starts to influence the electron behaviour below 10 keV. [62]). It was found that the characteristic angle alone was insufficient to quantify the discrepancy between the measurement and simulation.…”
Section: Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…This cut-off starts to influence the electron behaviour below 10 keV. [62]). It was found that the characteristic angle alone was insufficient to quantify the discrepancy between the measurement and simulation.…”
Section: Simulation Setupmentioning
confidence: 99%
“…Photons with energies larger than 0.22 MeV for the forward-directed benchmarks and 0.145 MeV for the angular distribution benchmarks were scored in 100 log spaced bins and compared with the published experimental benchmarks. 62,63 The tested physics constructors were Penelope, Livermore, Opt0, Opt3 and Opt4. A global production cut of 0.01 mm for secondary particles was used.…”
Section: E1 Simulation Setupmentioning
confidence: 99%
“…56 The physical models for electron and photon interactions differ between the codes and have been compared previously in various references. 46,50,52,57,58 Details of each code can be found in the respective manuals.…”
Section: Methodsmentioning
confidence: 99%
“…The reference codes were chosen based on their ability to produce results that agree closely with the experimental data for photon and electron beams and their capability to simulate IC response with high accuracy. 11,12,[51][52][53][54]…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the absorbed doses at the medium, D w,Q , and the detector, D c,Q , a series of Monte Carlo simulations were run with the main program penEasy [20]. This code is a main steering program that uses the PENELOPE system [17], a Monte Carlo general-purpose code designed for an accurate description of the coupled transport of photons, electrons and positrons in matter, with very good achievements at the material interfaces and for low energies [21][22][23][24][25]. The code has also been benchmarked for simulations of ionization chamber responses in calculations similar to those done in the present work [26,27].…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%